On the circumstellar envelopes of semi-regular long-period variables. Issue Volume 14:Issue S343(2019) (August 2018) - Díaz-Luis, J. J.; Alcolea, J.; Bujarrabal, V.; Santander-García, M.; Gómez-Garrido, M.; Desmurs, J.-F.
Abstract: The mass loss process along the AGB phase is crucial for the formation of circumstellar envelopes (CSEs), which in the post-AGB phase will evolve into planetary nebulae (PNe). There are still important issues that need to be further explored in this field; in particular, the formation of axially symmetric PNe from spherical CSEs. To address the problem, we have conducted high S/N IRAM 30 m observations of 12 CO J = 1−0 and J = 2−1, and 13 CO J = 1−0 in a volume-limited unbiased sample of semi-regular variables (SRs). We also conducted Yebes 40 m SiO J = 1−0 observations in 1/2 of the sample in order to complement our 12 CO observations. We report a moderate correlation between mass loss rate and the 12 CO(1−0)−to− 12 CO(2−1) line intensity ratio, introducing a possible new method for determining mass loss rates of SRs with short analysis time. We also find that for several stars the SiO profiles are very similar to the 12 CO profiles, a totally unexpected result unless these are non-standard envelopes.